A cross-sectional study to evaluate the effect of subjective sleep quality on autonomic functions in different age groups of adults - Jasrotia, Rajani Bala; Kanchan, Arvind; John, Nitin Ashok; Verma, Manish Kumar; Gangwar, Vibha (International Journal of Research in Medical Sciences, 2019)
Background: Poor sleep quality adversely affects the person’s homeostasis via combination of impairments to multiple physiological-mechanisms. Autonomic functions are important for different aspects of health and disease. Objective of study was to analyze the impact of subjective sleep quality on autonomic functions in different age groups of adults. Methods: A total of 375 apparently healthy adults from community were randomly selected for this cross-sectional observational study. They were divided into three groups based on the age distributions: Group 1: 18-30 years (n = 146); Group 2: 31-45 years (n = 112); and Group 3: 46-60 years (n = 117). Following assessments were done in all the participants in three groups: Anthropometric measurements, Pittsburgh Sleep-quality Index (PSQI), Electrocardiography (ECG), Autonomic functions based on frequency domain heart rate variability (HRV). Two-way analysis of variance followed by post hoc analysis was done for intergroup comparisons of all assessment characteristics. Spearman’s correlation was done to find the correlation coefficients between PSQI scoring and all other parameters mentioned above. Results: BMI, GPSQIS, SSQS, SDS and SMS were observed more in group2 and 3 as compared to group1, whereas SD and SE were more in group1 as compared to group 2 and 3. HF, Total Power and RR were more in group 1 as compared to group 3, whereas VLF and HR were less in group 1 as compared to group 3. LF/HF ratio and HR were more in group 3 as compared to group 2, whereas HF was more in group 2 as compared to group 3. There was statistically significant negative correlation between GPSQI and Total power, SMS and HF, SIT and HF, SD and LF/HF ratio, whereas statistically significant positive correlation between SMS and LF, SMS and LF/HF ratio, SIT and LF, SIT and LF/HF ratio, SD and total power as well as SE and total power. Conclusions: Ageing in adults affects the sleep-quality, reduces the sleep duration and decreases the sleep efficiency; these contribute to autonomic dysfunction as increased sympathetic activity and decreased parasympathetic activity in older adults as compared to younger adults.